The Small RNA sr8384 Is a Crucial Regulator of Cell Growth in Solventogenic Clostridia - Yang, Yunpeng (Appl Environ Microbiol, 2020)
Small RNAs (sRNAs) are crucial regulatory molecules in organisms and are well-known not only for their roles in the control of diverse crucial biological processes but also for their value in regulation rewiring. However, to date, in Gram-positive anaerobic solventogenic clostridia (a group of important industrial bacteria with exceptional substrate and product diversity), sRNAs remain minimally explored, and thus there is a lack of detailed understanding regarding these important molecules and their use as targets for genetic improvement. Here, we performed large-scale phenotypic screens of a transposon-mediated mutant library of Clostridium acetobutylicum, a typical solventogenic clostridial species, and discovered a novel sRNA (sr8384) that functions as a crucial regulator of cell growth. Comparative transcriptomic data combined with genetic and biochemical analyses revealed that sr8384 acts as a pleiotropic regulator and controls multiple targets that are associated with crucial biological processes through direct or indirect interactions. Notably, the in vivo expression level of sr8384 determined the cell growth rate, thereby affecting the solvent titer and productivity. These findings indicate the importance of the sr8384-mediated regulatory network in C. acetobutylicum. Furthermore, a homolog of sr8384 was discovered and proven to be functional in another important Clostridium species, C. beijerinckii, suggesting the potential broad role of this sRNA in clostridia. Our work showcases a previously unknown potent and complex role of sRNAs in clostridia, providing new opportunities for understanding and engineering these anaerobes. IMPORTANCE The uses of sRNAs as new resources for functional studies and strain modifications are promising strategies in microorganisms. However, these crucial regulatory molecules have hardly been explored in industrially important solventogenic clostridia. Here, we identified sr8384 as a novel determinant sRNA controlling the cell growth of solventogenic Clostridium acetobutylicum. Based on a detailed functional analysis, we further reveal the pleiotropic function of sr8384 and its multiple direct and indirect crucial targets, which represents a valuable source for understanding and optimizing this anaerobe. Of note, manipulation of this sRNA achieves improved cell growth and solvent synthesis. Our findings provide a new perspective for future studies on regulatory sRNAs in clostridia.